Sociodemographic correlates of cognitive performance in healthy children and adolescents - Mai, Elisabeth; Meigen, Christof; Schmidt, Ricarda; Ludwig, Juliane; Poulain, Tanja; Kiess, Wieland (Frontiers in Psychology, 2025)
BackgroundThe maturation of cognitive abilities, a key aspect of childhood development, is associated with numerous outcomes later in life. Socioeconomic variables have been shown to influence this developmental trajectory. Given the growing global socioeconomic inequality, it is essential to account for socioeconomic factors when conducting research on cognitive development. While previous studies often focused on single cognitive domains and small cohorts or age groups, this study aimed to assess the association between sex, maternal education, and cognitive performance using three standard cognitive tests in a large cohort of healthy children and adolescents and to explore Tetris as a game-based cognitive test.MethodsCognitive performance was examined in 9- to 19-year-olds using four tests (Trail Making Test, Mental Rotation Test, Continuous Performance Test, Tetris). Data were collected between October 2019 and December 2023 as part of the LIFE Child study, conducted in Leipzig (Germany), involving 770 participants for Tetris, Trail Making, and Mental Rotation, and 888 participants for the Continuous Performance Test. Multiple regression models, adjusted for age, considered sex and maternal education as independent variables.ResultsYounger boys showed lower attention and inhibition control than girls, but improved during puberty, ultimately outperforming girls in the Continuous Performance Test. In Tetris, boys cleared more lines but made more rotation and movement faults than same-aged girls. No sex differences were observed in the Trail Making and Mental Rotation Test. Children of mothers with higher education made fewer errors in the Mental Rotation Test and were more attentive and less impulsive in the Continuous Performance Test than children of mothers with lower education. Tetris performance was significantly associated with the Mental Rotation and Trail Making Test.ConclusionCognitive performance patterns varied by sex and maternal education, highlighting the importance of distinguishing typical developmental variation from cognitive delay to guide individual support. Lower maternal education emerged as a potential risk factor for poorer cognitive performance, relevant for targeted interventions. We recommend further investigating Tetris as a game-based cognitive test.